2005
DOI: 10.1016/j.jcf.2004.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term azitromycin treatment of cystic fibrosis patients with chronic Pseudomonas aeruginosa infection; an observational cohort study

Abstract: Long-term, low-dose AZ treatment in adult CF patients with chronic P. aeruginosa infection is safe and reduces the decline in lung function, increases weight, and reduces the percentage of mucoid strains of P. aeruginosa in sputum samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 29 publications
5
70
0
Order By: Relevance
“…Similar findings were reported for cystic fibrosis patients infected with P. aeruginosa (309)(310)(311), where improved lung function in children was seen following six to 15 months of azithromycin (AZM) treatment. This was an unexpected finding, considering the high levels of resistance that P. aeruginosa shows toward these drugs, and general anti-inflammatory effects associated with macrolides were suggested to account for the positive results (312).…”
Section: Antibiotics As Qs Inhibitorssupporting
confidence: 77%
“…Similar findings were reported for cystic fibrosis patients infected with P. aeruginosa (309)(310)(311), where improved lung function in children was seen following six to 15 months of azithromycin (AZM) treatment. This was an unexpected finding, considering the high levels of resistance that P. aeruginosa shows toward these drugs, and general anti-inflammatory effects associated with macrolides were suggested to account for the positive results (312).…”
Section: Antibiotics As Qs Inhibitorssupporting
confidence: 77%
“…The finding of a beneficial effect of azithromycin on pulmonary function has been reported in several smaller studies [26,[28][29][30]. A Cochrane review of macrolide therapy undertaken in 2004 concluded that treatment with azithromycin had a small but significant effect on pulmonary function in patients with cystic fibrosis [23].…”
Section: Clinical Trialsmentioning
confidence: 88%
“…In addition, gender, steroid treatment and macrolide treatment were identified as risk-indicator variables for serum total IgG levels. Long-term treatment with macrolide antibiotics was previously shown to positively affect lung function (Hansen et al, 2005;Anwar et al, 2008) and exert complex immunomodulatory effect (Shinkai et al, 2008;Steinkamp et al, 2008), which justified inclusion of this variable into our model. Surprisingly, macrolide treatment showed a positive and a negative relation to serum total IgG and FEV1, respectively, probably as a result of selection bias and little immunomodulatory effect.…”
Section: Inverse Relation Between Vitamin D and Serum Igg T Pincikovamentioning
confidence: 92%